Digital Trust in Online Platforms: A Bibliometric Review - Loso Judijanto (Westscience Press, 2026)
Digital trust has become a fundamental element in shaping user engagement, transaction reliability, and sustainable interactions across online platforms. As digital ecosystems continue to expand through social media, electronic commerce, and intelligent technologies, research on digital trust has grown rapidly and become increasingly interdisciplinary. This study aims to examine the intellectual structure, thematic evolution, and emerging trends in Digital Trust in Online Platforms through a bibliometric review approach. Bibliographic data were collected from the Scopus database and analyzed using VOSviewer to perform publication trend analysis, citation analysis, collaboration mapping, keyword co-occurrence, overlay visualization, and density analysis. The findings reveal that research in this field is centered on themes such as trust, social media, electronic commerce, consumer behavior, artificial intelligence, and data privacy. Collaboration analysis shows active global participation, with India, China, and the United States emerging as major contributors to scientific development. Temporal and thematic mapping indicates a transition from foundational discussions on trust and online interaction toward more advanced topics including AI-driven trust mechanisms, blockchain, machine learning, privacy governance, and secure digital infrastructures. This study provides a comprehensive overview of the current research landscape and offers future research directions for strengthening digital trust in increasingly complex online environments.